2014
DOI: 10.5194/isprsarchives-xl-3-w1-143-2014
|View full text |Cite
|
Sign up to set email alerts
|

Uav Photogrammetry to Monitor Dykes – Calibration and Comparison to Terrestrial Lidar

Abstract: ABSTRACT:Unmanned Aerial Vehicles (UAV) and photogrammetry are two fields that have been boosted these last years. Using aerial means, one can easily acquire aerial data and produce high resolution dense surface models, orthophotos,... IGN (the French Mapping Agency) and CNR (Compagnie Nationale du Rhône, which is the concessionary of the Rhône river and a hydraulic energy producer) have associated themselves on a thesis protect. The aim is to be able to monitor dykes from images acquired by UAV and take benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…To reduce the influence of the “human factor,” the same location (pixel coordinates) of georeferenced high contrast markers in the aerial 2D images was used across the four different software. The citations given alongside indicate other literature examples that have utilized these software in ecology research: 3DFlow Zephyr Aerial (little evidence of use in ecology, though widely used in urban environments, e.g., Vassena & Clerici, ; Peel, Luo, Cohn, & Fuentes, ; Azzola, Cardaci, Mirabella Roberti, & Nannei, ). Agisoft Photoscan (Cunliffe et al, ; Dandois et al, ; Hoffmann et al, ; Javernick, Brasington, & Caruso, ; Lucieer, Turner, King, & Robinson, ; Obanawa & Hayakawa, ). Pix4D (Magtalas, Aves, & Blanco, ; Ouédraogo, Degré, Debouche, & Lisein, ; Raeva, Filipova, & Filipov, ). MICMAC (Forsmoo et al, ; Lisein, Pierrot‐Deseilligny, Bonnet, & Lejeune, ; Ouédraogo et al, ; Tournadre, Pierrot‐Deseilligny, & Faure, ; Tournadre, Pierrot‐Deseilligny, & Faure, ). …”
Section: Methodsmentioning
confidence: 99%
“…To reduce the influence of the “human factor,” the same location (pixel coordinates) of georeferenced high contrast markers in the aerial 2D images was used across the four different software. The citations given alongside indicate other literature examples that have utilized these software in ecology research: 3DFlow Zephyr Aerial (little evidence of use in ecology, though widely used in urban environments, e.g., Vassena & Clerici, ; Peel, Luo, Cohn, & Fuentes, ; Azzola, Cardaci, Mirabella Roberti, & Nannei, ). Agisoft Photoscan (Cunliffe et al, ; Dandois et al, ; Hoffmann et al, ; Javernick, Brasington, & Caruso, ; Lucieer, Turner, King, & Robinson, ; Obanawa & Hayakawa, ). Pix4D (Magtalas, Aves, & Blanco, ; Ouédraogo, Degré, Debouche, & Lisein, ; Raeva, Filipova, & Filipov, ). MICMAC (Forsmoo et al, ; Lisein, Pierrot‐Deseilligny, Bonnet, & Lejeune, ; Ouédraogo et al, ; Tournadre, Pierrot‐Deseilligny, & Faure, ; Tournadre, Pierrot‐Deseilligny, & Faure, ). …”
Section: Methodsmentioning
confidence: 99%
“…() and is described step‐by‐step in the , to further facilitate the adoption and adaptation of the workflow described herein. Moreover, in the studies that have used MICMAC it has performed favourably when compared to validation data and/or other software on the basis of accuracy and robustness (Ouédraogo, Degré, Debouche, & Lisein, ; Tournadre, Pierrot‐Deseilligny, & Faure, ; Tournadre et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…MICMAC implements a range of different camera lens distortion models. The choice of camera lens calibration method has been shown to influence the accuracy of the resulting model produced by the SfM+MVS‐processing workflow (Tournadre et al., ). In this study, the Radial Extended camera calibration method was chosen, as it has been shown to perform well in other studies (Tournadre et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Van Iersel, Straatsma, Addink, and Middelkoop (); 12. Tournadre, Pierrot‐Deseilligny, and Faure (); 13. Young, Peschel, Penny, Thompson, and Srinivasan (); 14.…”
Section: River Corridor Remote Sensingmentioning
confidence: 99%